ACADEMIC MONITORING IN THE MEDICINE COURSE AS A LEARNING STRATEGY IN THE WEST OF THE BAHIA - da Fonseca, Alexandra Muniz Gomes; Marques, Maiara Bernardes (Brazilian Journal of Implantology and Health Sciences, 2023)
Introduction: The current scenario imposes changes and adaptations in medical course teaching, including the relationships between professors and students with the use of the new era of technology. In this sense, academic monitoring becomes an important activity where, in a mutual way, it enables the expansion of the didactic repertoire, development of the educator profile by the monitor, communication, body expression, professional planning, responsibility, leadership, and trust, among others. Experience report: The objective of this work is to report the experience of academic monitoring as an auxiliary learning strategy at a private university in Bahia, together with a curricular component that includes theory in the context of the discipline Biophysics for students of the 1st semester in the course of Medicine. This is a qualitative, descriptive study, of the experience report type on the activities carried out with academic monitoring. Weekly meetings were held with the subject’s guiding teacher, time was available for questions with the students, a clinical case was prepared and presented on the curricular component and objective activities of study review. Discussion: Monitoring becomes essential for the academic experience since it is the link between the scope of professors and students, transposing the roles of students in the position of professors, expanding the professional, interpersonal, creative perspective together with responsibility. The execution of this activity allowed the monitor to experience the responsibility of supervision, study guidance, clinical reasoning and reflection on the importance of communication in the education process. Final considerations: Therefore, given its complexity, teaching associated with monitoring proves to be effective for all involved. Also noteworthy is the need to publish more studies reporting experience in academic monitoring within the scope of the medical course.